IMPROVING THE VISCOSITY OF PARTIALLY HYDROLYZED POLYACRYLAMIDE (PHPAM) SOLUTION FOR ENHANCED OIL RECOVERY (EOR) APPLICATION - Arifin, Ihsan
Enhanced Oil Recovery (EOR) is a tertiary recovery technique performed on old wells. Without the recovery process, only 20-40% of oil can be exploited, while the rest (40-60%) is still left between the rocks. Therefore, it is necessary perform the primary, secondary and tertiary recovery processes. The technique is proven to produce a recovery factor of around 20%.1 In Indonesia, polymer injection in EOR techniques has not been applied due to economic issue because unavailability of domestically made polymers. In this research, synthesis of polyacrylamide was carried out with variation of acrylamide concentration and temperature. Addition polymerization was carried out using potassium persulfate (KPS) as initiator. Polyacrylamide was characterized by confirmation of functional groups using FTIR spectrum. It was found that polyacrylamide with greater Mv was produced in higher acrylamide concentration. A partial hydrolysis was carried out to polyacrylamide due to increase its viscosity. The results show that the viscosity of a 1000 ppm PHPAM solution at 25 °C can increase up to 145.22 cP which was initially 2.5 cP. These results indicate that PHPAM comparable with commercial polymers on the market.